Alternative sources of nitrogen for intensification of Zuri guineagrass production - Gonçalves, Janine Mesquita; Peron, Hugo Jayme Mathias Coelho; Costa, Luis Carlos Dias (Revista de Ciências Agroveterinárias, 2022)
The intensification of pasture production in Brazil is highly dependent on nitrogen fertilization. The aim was to evaluate the productivity of Zuri guineagrass in the management of successive cuts when submitted to intercropping with forage legumes and incorporation of organic residues in replacement of fertilization with urea. In four replication, a randomized complete block design was used, with six nitrogen sources (urea; cattle manure; chicken litter; forage radish; forage peanut; calopogonion and perennial soybean). The residues and urea were applied at the beginning of the experiment and the sowing of forage legumes was carried out on the same day as the grass. Three cuts were made in the grass when it reached 90 cm in height. The following parameters were evaluated: height, relative chlorophyll index, fresh and dry aboveground biomass, nitrogen concentration, protein percentage, and in the third cut, the number of tillers and tillering. It was also observed that there was a better guineagrass production, expressed by fresh and dry biomass indices, as well as with high production, regardless of the treatment used. It is possible to obtain a high growth rate and development of Zuri guineagrass, expressed by tillering and dry biomass production, with N supply using any of the nitrogen sources used.